Nuclear PRMT5, cyclin D1 and IL-6 are associated with poor outcome in oropharyngeal squamous cell carcinoma patients and is inversely associated with p16-status - Kumar, Bhavna (Oncotarget, 2017)
Protein arginine methyltransferase-5 (PRMT5) plays an important role in cancer progression by repressing the expression of key tumor suppressor genes via the methylation of transcriptional factors and chromatin-associated proteins. However, very little is known about the expression and biological role of PRMT5 in head and neck cancer. In this study, we examined expression profile of PRMT5 at subcellular levels in oropharyngeal squamous cell carcinoma (OPSCC) and assessed its correlation with disease progression and patient outcome. Our results show that nuclear PRMT5 was associated with poor overall survival (p < 0.012) and these patients had 1.732 times higher hazard of death (95% CI: 1.127–2.661) as compared to patients in whom PRMT5 was not present in the nucleus of the tumors. Nuclear PRMT5 expression was inversely correlated with p16-status (p < 0.001) and was significantly higher in tumor samples from patients who smoked > 10 pack-years (p = 0.013). In addition, nuclear PRMT5 was directly correlated with cyclin D1 (p = 0.0101) and IL-6 expression (p < 0.001). In a subgroup survival analysis, nuclear PRMT5-positive/IL-6-positive group had worst survival, whereas nuclear PRMT5-negative/IL-6-negative group had the best survival. Similarly, patients with p16-negative/nuclear PRMT5-positive tumors had worse survival compared to patients with p16-positive/nuclear PRMT5-negative tumors. Our mechanistic results suggest that IL-6 promotes nuclear translocation of PRMT5. Taken together, our results demonstrate for the first time that nuclear PRMT5 expression is associated with poor clinical outcome in OPSCC patients and IL-6 plays a role in the nuclear translocation of PRMT5.